Modalities of Healthcare Payment and their Consequences – A Qualitative Study on Kenyan Doctors - Yulu, Elijah; Brotherton, B Jason; Kamau, Geoffrey Gitau (KABARAK UNIVERSITY, 2019)
The Kenyan government has put a spirited reform to ensure all Kenyans get universal healthcare. This has led to restructuring of several entities among them the health insurance industry. This is geared at alleviating the burden of catastrophic expenditure on health from the poor Kenyans. However, insurance uptake remains at less than a quarter of the population with many Kenyans still paying for healthcare out-of-pocket. These out-ofpocket payers often don’t afford the ever-increasing cost of healthcare in Kenya. This study looked at how doctors deal with patients given their modality of payment. This was an online based survey that was distributed to Kenyan doctors via email by Kenya Medical Association. The survey sought information from the respondents on how they dealt with patients given their modality of payment. In addition, respondents were asked to provide an example of a case they had dealt with that touched on each payment modality. Respondents gave their experiences where insurance had influenced their clinical decisions. Codes developed from the prose were; “inability to pay”, “harmful to the patient”, “changed the prescription” among others Health insurance played a crucial role whenever respondents made decisions. Top on the list of things that the majority indicated would be considered is insurance status and/or their ability of patients to pay for the services. Respondents are stuck in a limbo; striving to give the best care to patients but limited by the patients’ inability to pay. In explaining their experiences, respondents explain a situation where they intend to offer the best, but patients cannot afford. This especially so for those without health insurance who end up either not getting services or at the very best, get inferior services
FULL TEXT
Keywords: Health insurance, Emergency medical care, Clinical decisions